СТАЛ ТА ПЕРСПЕКТИВА РОЗВИТКУ ЕСТЕТИЧНОЇ ОСВІТИ СТУДЕНТІВ ВИЩИХ НАВЧАЛЬНИХ ЗАКЛАДІВ (Педагогіка вищої та середньої школи, 2009)
Article is devoted the analysis of a modern condition and prospects of development of aesthetic formation of students of higher educational institutions, a substantiation of necessity of a formulation at youth of aesthetic outlook.